Associations between home insulin dose adjustments and glycemic outcomes at hospital admission. (May 2017) - Khan, Saira; Golden, Sherita Hill; Mathioudakis, Nestoras
Highlights: Home insulin doses are commonly reduced at admission. Insulin dose increases of 10–50% are associated with inpatient hyperglycemia, but not hypoglycemia. Weight-based insulin dosing may be preferred strategy for patients on home insulin doses of 0.4 units/kg/day or more. Abstract: Aims: To describe patterns of home insulin dose adjustments for non-surgical, non-critically ill patients at admission and to describe associations between these adjustments and inpatient glycemic control. Methods: Hospital records of non-critically ill patients treated with basal insulin prior to admission were identified. After exclusion of records in which a confounding factor influencing insulin dosing was present, 258 patient-admissions over a 3-year time period were included. Multivariate logistic regression was used to analyze the association between adjustments to home insulin total daily dose (TDD) and inpatient glycemic control within the first 48 h, adjusting for relevant confounders. Results: On hospital days 1 (HD1) and 2 (HD2), the home insulin TDD was reduced by 43.5% and 23.9%, respectively. Reductions in the home TDD ranging from 10% to 50% were not associated with normoglycemia or hyperglycemia, whereas increases ranging from 10% to 50% were associated with 2–5-fold increased odds of hyperglycemia. For patients with home insulin TDD ≥0.4 units/kg/day, a weight-based dose of 0.4–0.6 units/kg/day was associated with significantly higher odds of normoglycemia on HD2 (OR 3.99; 95% CI 1.42–11.21) compared to lower doses. Conclusions: Compared to less aggressive increases, home insulin dose increases ranging from 10% to 50% were associated with greater odds of hyperglycemia without increased odds of hypoglycemia during early hospitalization. Weight-based insulin dosing may be a preferred strategy for glycemic control among patients whose home TDD is ≥0.4 units/kg/day.